Evaluation of MeTree for Family Health History Collection in Sri Lanka - Hu, Ruoyu; De Silva, Vijitha; Orlando, Lori; Østbye, Truls (Asian Pacific Journal of Cancer Biology, 2022)
Introduction: Information about family history of illnesses including hereditary cancers is increasingly important to ensure each patient receives optimal health promotion advice, preventive health services and appropriate screening or treatment. MeTree is an American, validated, web-based family health history based risk assessment tool that collects data directly from patients. Little is known about its utility in countries with different disease profiles, health care infrastructure and policies, and cultural and socioeconomic contexts. Methods: This study enrolled 304 medical students from the University of Ruhuna in Sri Lanka. Participants constructed family pedigrees and entered their information into MeTree, as well as completed a paper-based questionnaire asking about their experience with and perceived benefits of MeTree. Results: 3302 records and 87 different diseases were entered into MeTree for all index participants and their relatives. Diabetes was the most common disease reported and accounted for 24.6% of all diseases reported. The mean time to enter information into MeTree was 36.3 minutes. Questionnaire responses indicated a high level of satisfaction with the use of MeTree and the perceived benefit was high. No significant difference was observed in completion time or survey responses by age or gender. Conclusions: Most medical students found MeTree easy to complete and considered it a useful experience. The majority thought it possible to generalize MeTree to the context of Sri Lanka, though barriers, such as limited internet access, will need to be addressed to integrate a web-based tool, like MeTree, into routine practice in Sri Lankan clinics.